Rodat: Budaya Tradisi Yang Berevolusi: Rodat: Traditional Culture which Evolves - Muhammad Irfan Nyia Abdullah, Sakinah Abu Bakar dan Tasnim Mohd Annuar, (Wacana Seni Journal of Arts Discourse, 2013)
Rodat is one of the traditional cultures of the Malays which can be found in Terengganu. Combining the elements of music, dance and song, rodat in Kuala Terengganu has undergone many changes. The objective of this research is to identify the evolution that has taken place in the art of rodat in Kuala Terengganu from the aspects of its functions, costumes, songs, lyrics, performance structure, number of group members and the acceptance of the public. The data for this research was collected through two methods which are field observation and literature research. The art of rodat in Kuala Terengganu is slowly losing its place in society and may perish. Therefore, rodat needs to be introduced to the younger generation through the curriculum in educational institutes, and commercialised at the national level via the organisation of rodat festivals and specific programmes by the state of Terengganu so that this beautiful art form can be preserved as a national treasure which should be protected.